Molecular and immunological characterization of glycolytic enzymes : FBA and GAPDH-1 of Neisseria meningitidis - Tunio, Sarfraz Ali (2010)
There is growing evidence that several glycolytic enzymes, so-called housekeeping enzymes, including fructose bisphosphate aldolase (FBA) and glyceraldehyde 3-phosphate dehydrogenase (GAPDH), despite being devoid of any apparent secretion signal, may be localised to the cell surface of several bacterial and fungal species, where they exhibit diverse non-glycolytic biological functions. However, the mechanism(s) of secretion of such signal-less proteins to the cell surface or to external environment is not well understood. Whilst their intracellular functions are well known, it is unclear whether they perform any additional functions, unconnected to their central role in glycolysis, on the bacterial surface. It is becoming apparent that such proteins may be immunogenic and they may be capable of eliciting protective immunity in animal models. As such, they represent potential vaccine candidates. In a search for novel surface exposed proteins as potential vaccine candidates against N. meningitides serogroup B, and in accordance with the fact that glycolytic enzymes are putative virulence factors in some bacterial species, it is hypothesised that meningococcal FBA and GAPDH-l, may be present on the cell surface and thus may contribute to the pathogenesis of disease. In N. meningitidis serogroup B, there is a single gene cbbA (NMB 1869) and two genes gapA-l and gapA-2, predicted to encode fructose bisphosphate aldolase and glyceradehyde 3-phosphate dehydrogenase (GAPDH) enzymes, respectively. Sequence analysis shows that FBA and GAPDH-l are highly conserved at the amino acid level. The amino acid sequences of FBA from N. meningitidis and those from Xanthobacter flavus and Synechocystis sp. displayed high identities (67 and 65%, respectively), which suggests that the meningococcal FBA (like those of X flavus and Synechocystis sp.) belongs to bacterial Class-II FBP aldolases. The cbbA and gapA-l genes were cloned and over-expressed in host E. coli. FBA was purified under non-denaturing and denaturing conditions, whilst GAPDH-l was purified under denaturing conditions. Recombinant native FBA was used in a coupled enzymic assay confirming that it has fructose bisphosphate aldolase activity. The purified FBA and GAPDH-l proteins were then used to raise polyclonal monospecific rabbit antiserum (RaFBA and RaGAPDH-l) for subsequent characterisation of enzymes with the aim to determine their subcellular localization as well as potential roles in pathogenesis of meningococcal disease. RaFBA and RaGAPDH-l reacted with ca. 38-kDa and 37-kDa proteins, respectively, in immunoblot analysis against whole cell lysates from meningococcal strain MCS8 but not the cbbA and gapA-l isogenic mutants, respectively, confirming that cbbA and gapA-l are naturally-expressed proteins in N. meningitidis. Furthermore, expression of cbbA was detected in 26/26 and GAPDH-l in 17/17 diverse meningococcal strains. Cell fractionation experiments showed that meningococcal FBA and GAPDH-l are localized both to the cytoplasm and to the outer membrane. These results were validated by flow cytometry. The data demonstrated that outer membranelocalized FBA was surface-accessible to FBA-specific antibodies in encapsulated N. meningitidis, whereas flow cytometry analysis confirmed that GAPDH-I could be detected on the cell surface, but only in a siaD-deficient background, suggesting that GAPDH-I is inaccessible to antibody in encapsulated meningococci. Mutational analysis and functional complementation was used to identify additional functions of FBA and GAPDH-l. The cbbA and gapA-l knock-out mutant strains were unaffected in their ability to grow in vitro, but showed a significant reduction in adhesion to HBME and HEp-2 cells compared to their isogenic parent and complemented derivatives. In a transgenic mouse model, cbbA mutant strains were shown to be less able to establish bacteraemia compared to their wild-type parent strains. In summary, in this study, expression of FBA and GAPDH-l was shown to be well conserved across diverse isolates of Neisseria species. This study also demonstrates for the first time that meningococcal glycolytic enzymes, FBA and GAPDH-l. are surface localised proteins and required for optimal adhesion of meningococci to host cells. Taken together, these results suggest that FBA and GAPDH-l may be involved in the pathogenesis of meningococcal disease.